2017
DOI: 10.21608/jfds.2017.37125
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Transglutaminase Isolated from Rosemary Leaves, and Development of Chemical, Rheological and Sensory Properties of Kareish Cheese Made with Transglutaminase.

Abstract: Purification of transglutaminase (TGase) isolated from leaves of rosemary (Rosmarinus officinalis L) carried out by three steps including protein precipitation with using ammonium sulfate (40-80%), followed by elution into ion exchange column (DEAE-Sephadex A-50). The further purification of dialyzed fractions were applied on Sephadex G-100. The purified enzyme eluted from gel filtration column (Sephadex G-100) had 26.51 yield associated with increased about 6.3 in fold of purification. The optimum pH for rose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
3
6
0
Order By: Relevance
“…It was also observed that the pH of all samples significantly decreased during the storage time due to the conversion of lactose to lactic acid by microorganisms (D'Alessandro et al, 2019) and production of free fatty acids through lipid oxidation. Similar results regarding the effect of oxidation and lactic acid production by microorganisms in reducing pH were reported by Darwish andTaher (2017) andD'Alessandro et al (2019). reported that samples treated with TGase had the most changes in their water content and hardness due to covalent bonds formed by TGase.…”
Section: Phsupporting
confidence: 85%
See 2 more Smart Citations
“…It was also observed that the pH of all samples significantly decreased during the storage time due to the conversion of lactose to lactic acid by microorganisms (D'Alessandro et al, 2019) and production of free fatty acids through lipid oxidation. Similar results regarding the effect of oxidation and lactic acid production by microorganisms in reducing pH were reported by Darwish andTaher (2017) andD'Alessandro et al (2019). reported that samples treated with TGase had the most changes in their water content and hardness due to covalent bonds formed by TGase.…”
Section: Phsupporting
confidence: 85%
“…Many researches have been conducted to investigate the effect of direct TGase addition on functional properties of different cheeses including white fresh cheese (García-Gómez, Vázquez-Odériz, Muñoz-Ferreiro, Romero-Rodríguez, & Vázquez, 2019), semi-hard cheese (Darnay, Králik, Oros, Koncz, & Firtha, 2017), edam cheesemaking (Aaltonen, Huumonen, & Myllärinen, 2014), trappist cheese (Darnay, Králik, et al, 2017;Darnay, Tóth, et al, 2017), donkey cheese (D'Alessandro, Martemucci, Loizzo, & Faccia, 2019), low-fat gouda-like cheese (Ahmed, El-Nimer, Mostafa, & Omar, 2015), low-/high-fat mozzarella cheese (Metwally, El-Zeini, & Gazar, 2018), and kareish cheese (Darwish & Taher, 2017). It has been reported that the incorporation of encapsulated enzymes can eliminate the problems related to free enzyme addition (Kailasapathy & Lam, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, the addition of 1.0% S. platensis was found to approximately double the antioxidant capacity from 7.68 to 15.03 mM TE on day 1 of storage. Research indicates that the antioxidant activity and phenolic content in dairy products, including yogurt, cheese, ice cream, and fermented milk, show an elevation in the presence of microalgae (O'Sullivan et al, 2014;Barkallah et al, 2017;Darwish, 2017;Szmejda et al, 2018;Atallah et al, 2020;Aydemir and Öner, 2020). S. platensis, one of the most important microalgae, has been used as a food in Asian countries for a long time due to its high nutritional value and is gaining importance in European countries.…”
Section: Evaluation Of Total Antioxidant Activity and Phenolic Contentsmentioning
confidence: 99%
“…Moreover, a trend has begun to add microalgae (cyanobacterial biomass) in fermented milk products to increase the functional product properties by promoting the viability of probiotics and also to improve their nutritional properties (Varga et al 2002;Beheshtipour et al 2013). Spirulina is frequently used for human consumption in various forms: tablets, capsules, or food additives such as dairy products (Varga et al 2002;Guldas and Irkın 2010;Malik et al 2013;Agustini et al 2016;Barkallah et al 2017;Darwish 2017;Szmejda et al 2018;Çelekli et al 2019;Narayana and Kale 2019;Çelekli et al 2020;Bosnea et al 2021), gelatin desserts (Gouveia et al 2008), and bakery products (De Marco et al 2014;Ashoush and Samar 2019;Grahl et al 2020;Da Silva et al 2021).…”
Section: Introductionmentioning
confidence: 99%